O presidente negro: um outro olhar - Campos, Luiz Carlos de Sá (2011)
In The Black President, Monteiro Lobato abandons realist prose Urupês City, dead and Negrinha to debut in science fiction, a journey through time. The book is regarded by some as the "Bible of the future" but is little studied by scholars and critics of Lobato, probably because it is a contentious issue, and that may well be read as a lampoon racist. Portrays the current scientific and intellectual debate in the early decades of the twentieth centur y, but is also produced with the aim of launching the author on an international career, ambition clearly seen in his correspondence with Rangel. In it, Monteiro Lobato is clear that the black president was part of a project to make it a writer and editor in North America since losing ground as a writer and the economic and political crises that affected the Brazilian society in the 1920, made the continuity of his work as editor. In his letters, however, it is observed that the loss of editor who helped design his name not only represented his financial ruin, but also the end of the literary status attributed to it the power to consecrate new writers and their works, the value literary, without thinking about the profits of that operation.